HTHQ (1- O-hexyl-2,3,5-trimethylhydroquinone), an anti-lipid-peroxidative compound: its chemical and biochemical characterizations - Hino, Tadayuki; Kawanishi, Shinya; Yasui, Hiroyuki; Oka, Shigenori; Sakurai, Hiromu (Biochimica et biophysica acta, 1998)
Recently, it has become apparent that reactive oxygen species (ROS) play many important roles in biological systems. For example, relationships between many diseases, such as cancer, cardiac infarction and arteriosclerosis, and ROS have been found. It is also well known that anti-oxidative agents scavenge ROS in biological systems, which in turn prevents ROS-related diseases. In our previous efforts to develop effective anti-oxidative compounds, we found that 1- O-hexyl-2,3,5-trimethylhydroquinone (HTHQ), which is a hydroquinone monoalkyl ether, is a potent anti-oxidative agent. Here, the scavenging activities of HTHQ against ROS, such as superoxide anion radicals, hydroxyl radicals, t-butyl peroxyl radicals and singlet oxygens, were examined by the ESR (electron spin resonance)-spin trapping method. Among ROS, HTHQ scavenged t-butyl peroxyl radicals most effectively (IC 50=0.31±0.04 mM), showing approximately twice the activity of a well-known lipophilic anti-oxidant, d, l-α-tocopherol (IC 50=0.67±0.06 mM), as measured by IC 50 values defined as the 50% inhibition concentration of the generated ROS. In addition, a relatively stable ESR spectrum of free radicals due to HTHQ was observed during the reaction of HTHQ and t-butyl peroxyl radicals, indicating a direct reaction of HTHQ and t-butyl peroxyl radicals. The free radicals due to HTHQ were more stable than those derived from d, l-α-tocopherol under the same conditions examined. On the basis of these results, we evaluated anti-lipid-peroxidative activity of HTHQ in three systems involving micelles, liposomes and rat liver microsomes. HTHQ exhibited a similar anti-oxidative activity to that of d, l-α-tocopherol against lipid peroxidation in linolate micelles initiated by addition of Fe 2+. On the other hand, HTHQ exhibited approximately 4.8-fold higher anti-lipid-peroxidation activity than that of d, l-α-tocopherol against the peroxidation in phosphatidylcholine liposomes initiated by addition of Fe 2+. Furthermore, HTHQ scavenged the lipid peroxides at a rate approximately 150 times higher than that of d, l-α-tocopherol against Fe 3+-ADP-induced lipid peroxidation in rat liver microsomes, indicating that the anti-lipid-peroxidation activity of HTHQ might be substantially elevated in biological systems in comparison with that of d, l-α-tocopherol. Based on these results, we suggest that HTHQ reacts directly with peroxyl radicals, such as t-butyl peroxyl radicals and peroxides of linolate micelles, liposomes and microsomes, by scavenging them to form stable free radicals. The resulting free radicals are presumed to be reduced by several reducing mechanisms in biological systems similarly to those of d, l-α-tocopherol, and then the lipid-peroxidation reactions will be terminated. In conclusion, HTHQ was found to be a potent anti-lipid-peroxidative compound and its anti-oxidation activity to be extremely elevated in biological systems, such as that of liver microsomes via the generation of stable free radicals. We propose that HTHQ is a potent anti-oxidative agent for use in future treatments for lipid-peroxide relevant diseases.